2022
DOI: 10.1001/jamanetworkopen.2022.18167
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Patient Protection and Affordable Care Act With Ambulatory Quality, Patient Experience, Utilization, and Cost, 2014-2016

Abstract: Key Points Question How were ambulatory quality, patient experience, utilization, and cost associated with implementation of the Patient Protection and Affordable Care Act (ACA)? Findings In this nationally representative cross-sectional study of 123 171 individuals, the ACA was associated with more high-value diagnostic and preventive testing, improved patient experience and access, and decreased out-of-pocket expenditures for lower income US individuals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…These findings align with other studies showing improved health outcomes following ACA implementation [11][12][13]. For instance, a study by Sommers et al (2017) found that the ACA improved conditions for patients with chronic conditions, including cancer, potentially contributing to better survival rates [14]. Another study by Siegel et al (2017) reported improvements in cancer survival rates post-ACA, emphasizing the role of early detection and access to care [15].…”
Section: Impact Of Aca On Cancer-specific Survivalsupporting
confidence: 84%
“…These findings align with other studies showing improved health outcomes following ACA implementation [11][12][13]. For instance, a study by Sommers et al (2017) found that the ACA improved conditions for patients with chronic conditions, including cancer, potentially contributing to better survival rates [14]. Another study by Siegel et al (2017) reported improvements in cancer survival rates post-ACA, emphasizing the role of early detection and access to care [15].…”
Section: Impact Of Aca On Cancer-specific Survivalsupporting
confidence: 84%
“…In addition, our study spanned several years with influential policy implementation, such as the 2014 Affordable Care Act expansion; however, previous studies have found little or no change in quality over long-term follow-up for ambulatory care following this implementation. 36 An additional limitation of the study is a follow-up period of 1 year. However, adjusting the follow-up period to 2 years did not statistically change the results (eTable 3 in Supplement 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare systems regularly navigate a variety of external stressors, including policy changes, natural disasters, workplace violence committed by patients or other community members, and emerging infectious diseases [1][2][3][4] . These phenomena threaten usual delivery of patient care, and while strategies exist to anticipate and manage these challenges 5 , there is a lack of data regarding how health care systems experience and address concurrent organizational stressors.…”
Section: Introductionmentioning
confidence: 99%